Analysis of Regional Asset Management Information System Application For Medan City Library Assets and Archive Services - Nurfi, Indah; Nasution, Yenni Samri Juliati; Hasibuan, Nur Fadhilah Ahmad (Yayasan Sinergi Kawula Muda, 2024)
The purpose of this study is to implement the Regional Asset Management Information System on the assets of the Medan City Library and archive services. This research uses qualitative methods to collect data and information. This study aims to find out the implementation of the Regional Asset Management Information System which is still carried out manually, as well as the complicated procedures for deleting assets. In addition, this study also found challenges in the implementation of accounting information systems, such as errors in the grouping of goods. The results of this study show that the Application Regional Asset Management Information System is still not optimal in its use, because there are still menus that do not exist or cannot be used, such as minute menus and item deletion menus, This needs to be considered so that the processing of financial statements can run smoothly, effectively and efficiently. By offering a new perspective on how Regional Asset Management Information Systems Applications are used, this study adds knowledge in the field of accounting information systems. The results of this study are expected to be used by accounting practitioners and other researchers to be able to improve the Regional Asset Management Information System Application periodically so that the existing data is more accurate.